Association between overweight and obesity with stress amongst Iranian adolescents living in Malaysia - Juni, Muhamad Hanafiah; Babazekri, Leila; Mohd Zulkefli, Nor Afiah; Azman, Ahmad Zaid Fattah (Community Health Society Malaysia, 2014)
Background: In recent decades, the prevalence of obesity among adolescent has risen worldwide. Obesity has been reported to be increasing in developing countries and undergoing nutritional transition, and also in developed countries. Stress had been reported associate with development and maintenance of adolescent overweight and obesity. Objective: The objective of the study is to determine the mean difference of stress score with overweight and obesity amongst Iranian adolescents living in Malaysia. Materials and methods: 161 respondents aged 14 to 18 years old whom were attending Iranian schools in Kuala Lumpur, Malaysia were recruited in this cross sectional study which was conducted in September 2013. The respondents were randomly selected from list of students aged 14 to 18 years enrolled in the Iranian schools by random sampling method and using random number table. Self-administered questionnaire was employed in the study. The questionnaire consists of socio demographic information of respondents and DASS21 questionnaire were used to assess stress score of the respondent’s. The weight and height of respondent’s were taken with SECA weighing with height equipment. The data was analyzed using SPSS version 21. Results: The result showed that prevalence of overweight and obesity among Iranian adolescents studied was 49.7%. The study revealed that the mild level of stress amongst adolescents was 13.1% and moderate was 3.8%. The study also showed that there was a significant difference between mean score of stress with overweight and obesity (t=4.72, P=0.001 and 95%CI= 4.79 – 1.95). With regards to gender, only male adolescents showed significant difference between mean score of stress with overweight and obesity (t=5.31, P=0.001, 95%CI= 6.28 – 2.86). Conclusion: Iranian adolescents aged 14 to 18 years old showed significant difference between mean score of stress and status of Body Mass Index.